Reforming regulatory relationships: The impact of medical revalidation on doctors, employers, and the General Medical Council in the United Kingdom. Issue 4 (9th January 2019) - Tazzyman, Abigail; Bryce, Marie; Ferguson, Jane; Walshe, Kieran; Boyd, Alan; Price, Tristan; Tredinnick‐Rowe, John
Abstract: In 2012, medical regulation in the United Kingdom was fundamentally changed by the introduction of revalidation – a process by which all licensed doctors are required to regularly demonstrate that they are up to date and fit to practice in their chosen field and are able to provide a good level of care. This paper examines the implications of revalidation on the structure, governance, and performance management of the medical profession, as well as how it has changed the relationships between the regulator, employer organizations, and the profession. We conducted semi‐structured interviews with clinical and non‐clinical staff from a range of healthcare organizations. Our research suggests that organizations have become intermediaries in the relationship between the General Medical Council and doctors, enacting regulatory processes on its behalf and extending regulatory surveillance and oversight at local level. Doctors' autonomy has been reduced as they have become more accountable to and reliant on the organizations that employ them.